International connections of the Ecuadorian Amazonian forest colonization process 1960-1970 - Pablo Campaña (Íconos)
This article exposes the various international influences that –between 1960-1970- operated in order to stimulate peasant migration towards the Ecuadorian Amazonian frontier. During that period poor farmer organizations in several Latin American countries were demanding access to land held by traditional latifundia. In order to defuse the revolutionary potential of these claims, the Organization of American States (OAS) came up with a plan that would have the peasants migrate as colonists towards jungle areas, such as Amazonia. A central topic of the present text is the study of the several international connections between this organization and United States diplomacy in their efforts to boost colonization policies in the Ecuadorian Amazonian frontier. In a first stage, Ecuador received loans from foreign financial organizations, which were targeted for the construction of roads that would facilitate access to the rainforest areas. This was a major component of early efforts to promote the occupation of the tropical woodlands. Additionally, strong pressure by US diplomacy forced Ecuador to pass legislation facilitating colonization, while, at the same time, the Inter American Institute of Agrarian Sciences (IICA), trained government officials in the skills necessary to implement and enforce these policies. The article uses diplomatic, legal and bureaucratic reports in order to disclose the administrative transnational strategies that were active in promoting the migration of landless peasants towards the Amazonian wilderness, as part of an effort to neutralize the risk of communist political revolutions.